Carbon Monoxide (CO) Exposure to Health Risks for Street Vendors in Trade Centers, Traditional Five Bridges - Veza Azteria; Karolina Mulyati Natul; Erna Veronika; Mayumi Nitami (Window of Health : Jurnal Kesehatan, 2026)
Carbon monoxide (CO) exposure from motor vehicle emissions is a major environmental health concern for street vendors with prolonged outdoor activities. This study aimed to assess the health risks of CO exposure among street vendors in the Jembatan Lima Market, West Jakarta. A descriptive cross-sectional study was conducted using the Environmental Health Risk Analysis (ARKL) approach. CO concentrations were measured over three days using an Indoor Air Quality Monitor. The results showed CO concentrations ranging from 3.43 to 21.98 mg/m³, with an average of 12.91 mg/m³. Risk characterization indicated that real-time exposure was within safe limits (RQ ≤ 1). However, lifetime risk analysis demonstrated potential non-carcinogenic health risks, with Risk Quotient (RQ ≥ 1) occurring from the 10th year at maximum concentrations and from the 15th year at average concentrations. These findings indicate that long-term CO exposure may pose significant health risks to street vendors.